Family Therapy and Young Abusers: Experiences from the multi-agency treatment service TVERS in Vest-Agder County, Norway (Journal of Comparative Social Work, 2009)
This article focuses on young abusers participating in a treatment program for families where one or more children have experienced child sexual abuse and/or have abused other children. TVERS is a multiprofessional team where the treatment is performed within a frame of control ,“care and control hand in hand”. Three trained family therapists from three different agencies come together and form the therapy. The caseworker from the child care protection service (Children`s Service) becomes a part of the TVERS-team during their therapeutic work with the young abuser and his family. The therapists are given access to all reports and documents from the police, the court and medical services. The caseworker can follow up the family between appointments as well as initiate child protection procedures if necessary. The article describes our experience of working with families where the son in the family has abused other children outside or inside their own family.